2023
DOI: 10.3390/nu15030669
|View full text |Cite
|
Sign up to set email alerts
|

Contribution of Proteins to the Latin American Diet: Results of the ELANS Study

Abstract: Dietary protein intake is vital to life. Here we sought to characterize dietary sources of protein in eight Latin American countries. Survey data were collected for Estudio Latinoamericano de Nutrición y Salud (ELANS); participants were from Argentina, Brazil, Chile, Colombia, Costa Rica, Ecuador, Peru, and Venezuela (n = 9218, 15–65 years old). The primary aim of this analysis was to quantify per-person daily protein consumption by country and sociodemographic factors. Secondary aims: to quantify proportional… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 31 publications
0
6
0
Order By: Relevance
“…Argentina is a significant contributor to global beef production, accounting for approximately 5% of the total global output, and is one of the countries with the highest per capita meat consumption ( 40 ). In fact, animal-based proteins account for nearly 70% of the total daily protein intake ( 41 ). Additionally, it was the country with the highest processed food such as soft drinks, cookies and crackers, pizza, sugar and sweets, processed beef, cakes, salad dressing, and ice cream, many of which are sources of fat, in parallel it was country with the lowest consumption of fruits, legumes, rice, roots, and fish ( 39 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Argentina is a significant contributor to global beef production, accounting for approximately 5% of the total global output, and is one of the countries with the highest per capita meat consumption ( 40 ). In fact, animal-based proteins account for nearly 70% of the total daily protein intake ( 41 ). Additionally, it was the country with the highest processed food such as soft drinks, cookies and crackers, pizza, sugar and sweets, processed beef, cakes, salad dressing, and ice cream, many of which are sources of fat, in parallel it was country with the lowest consumption of fruits, legumes, rice, roots, and fish ( 39 ).…”
Section: Discussionmentioning
confidence: 99%
“…The agricultural industry in Peru has shown significant growth over the past decades, making it the second-largest economic sector in the country ( 43 ); thus, fresh food products are important in the Peruvian diet. In this case, grains, bread, pasta, potatoes, whole grain products, fruits, and vegetables were the principal contributors to the total EI ( 39 ), whereas poultry was the main protein source ( 41 ).…”
Section: Discussionmentioning
confidence: 99%
“…Some LMIC may not be suitable for raising livestock; for example, West Africa is unlikely to support cattle due to the risk of tsetse fly infestation [ 45 ]. Central and South America, where cattle consumption is high, face the consequences of unsustainable land, water, and energy usage, and high greenhouse gas emissions [ 46 ]. From the health perspective, high consumption of red meat like beef, as opposed to other ASFs, such as dairy and eggs, also increases risk of ischemic heart disease [ 47 ].…”
Section: Diets and Protein Sources In Lmicmentioning
confidence: 99%
“…Currently, the main staple crop in Latin America is wheat, with various legumes eaten in all parts of the region [ 58 ] ( Table 3 ). A study in 2015 by the Estudio Latinoamericano de Nutrición y Salud (ELANS) found that, in 8 Latin American countries, ∼65% of daily protein was animal-based whereas 35% was plant-based [ 46 ]. The plant-based protein groups with the highest contribution to protein consumption were grains, legumes, then nuts, and seeds.…”
Section: Diets and Protein Sources In Lmicmentioning
confidence: 99%
See 1 more Smart Citation